Elucidating the genetic architecture of reproductive ageing in the Japanese population - Momoko Horikoshi (Nature Portfolio, 2018)
The timing of female reproductive capacity is influenced by genetic and environmental factors. Here, in genome-wide association studies, the authors identify genetic loci for age at menarche and onset of menopause in Japanese women, and highlight differences with European populations.